ANALISIS PROFITABILITAS UMKM BERBASIS KULINER PRODUK LOKAL DI MASA PERALIHAN PANDEMI MENUJU ENDEMI - Yusnita, Rita Tri; Fitriadi, Budhi Wahyu (JURNAL EKONOMI PERJUANGAN, 2024)
This study aims to analyze the profitability of MSMEs based on local culinary products in the city of Tasikmalaya, especially during pandemic and endemic times, with the aim of seeing whether there are significant differences between the financial performance of MSMEs during pandemic and endemic times. The emergence of the global Covid-19 pandemic outbreak has had an impact on business activities so that it has affected sales levels and has had an impact on company profits. Restrictions on economic activity during the pandemic began to be relaxed during the endemic period. The method used in this study is descriptive and quantitative comparative analysis, with a survey approach where a sample of 55 local culinary-based MSME groups is taken which are considered representative, using a purposive sampling technique, from a population of 545 culinary-based MSME groups in the city of Tasikmalaya. The data analysis tool used in this study was the Wilcoxon signed test. The results of the study show that in general the profitability of MSMEs during the pandemic can still be said to be quite good, although there are several MSMEs that have negative profitability values. In general, the profitability of MSMEs during endemic times can be said to be good, and there are no more MSMEs that have negative profitability values. There is a significant difference between the profitability of MSMEs during pandemic and endemic periods.